The Dynamic Effects of the February 6 Kahramanmaraş Earthquakes on Economic Growth: An ARDL Analysis Based on Earthquake Scores (Third Sector Social Economic Review, 2025)
The Turkish economy attracts attention due to its vulnerability to macroeconomic external shocks, such as the frequent earthquakes it faces. The earthquakes in Kahramanmaraş on February 6, 2023, have greatly impacted economic growth. They caused both direct and indirect effects, along with significant human losses. This study aims to measure the impact of the February 6 earthquakes on economic growth by utilizing an earthquake score (earthquake loss intensity) and to analyze the relationship in both the short and long term by using the ARDL approach. The analysis contains quarterly data from 2003:Q1 to 2025:Q1. The earthquake score, which measures the intensity of damage caused by the earthquake, has been taken into account in both the human and economic damage dimensions. Furthermore, the macroeconomic effects through post-earthquake reconstruction and public investment expenditure channels were examined. As a result, findings were obtained indicating that the February 6 earthquakes had a positive impact on economic growth in the first quarter after the earthquake, but an adverse effect on the second quarter. In the long term, it was found that public investment expenditures after the earthquake harmed economic growth. Studies on disaster economics in Turkey are limited, and comprehensive analyses that measure both human and economic damage through earthquake scores are rare in the literature. The fact that the integrated impact has not been examined before, particularly in Turkey, adds novelty and originality to the study in terms of both methodology and policy recommendations.
Keywords: Earthquake; earthquake score; economic growth; investment spending; ARDL Analysis